Kekuatan Hukum Kreditur Hak Tanggungan Peringkat Kedua dan Seterusnya - Nur Hidayati; Ana Silviana (Universitas Batanghari Jambi, 2023)
Basically, everyone in the company faces various needs on a daily basis. These needs vary, some need to be prioritized, some are secondary, and some can only be met later. In the course of this development, of course, industrial and trade activities resulted in an increase in the funding sector, and not all entrepreneurs had sufficient capital. So from here the creation of a credit transaction. As credit transactions progress, problems sometimes occur, one of which is bad debts by debtors whose collateral has been upgraded to second place, with various factors because the debtor is unable to pay, and other economic factors. certainty that the creditor must have legal force in the execution of the guarantee. The problem of this research is, the strength of the creditor as the second rank mortgage holder and so on if the debtor is in default. The research method used is a normative research method using an approach that is an approach to applying laws and conceptualizing. The conclusion of the research is the strength of the creditor as the second rank mortgage holder if the debtor defaults, so the legal power of the creditor in the execution of the second rank mortgage guarantee, both parties have a basic agreement that binds them, in an agreement that contains an agreement between the debtor and creditor which if the debtor defaults, then the creditor as the second rank mortgage holder and so on has strong legal force and great influence.